Pengaruh Pertukaran Sosial terhadap Kinerja dan Turnover Intention Sebagai Mediasi - Galuh Gian Vinda (EKONOMI DAN BISNIS DIGITAL, 2022)
The purpose of study: This study aims to determine the effect of the relationship between social exchange, turnover intention on performance appraisal.Methodology: The method in this study uses the Accidental Sampling method. This research is a quantitative research, the sample in this study is 72 employees. The data collection technique was done by using a questionnaire.Result: The results of this study are, Social Exchange has a significant positive effect on Turnover Itention. Social Exchange has a significant positive effect on Performance Assessment Turnover Itention has a significant positive effect on Performance Assessment.Keyword : Social Exchange, Turnover Intention On Performance Appraisal.